Food diversity of three ethnic groups: a case study from Xieng Khuang province, Northern Lao PDR - Pathumphone, Sonemany; Sanitchon, Jirawat; Polthanee, Anan; Promkhambut, Arunee (Asia-Pacific Journal of Science and Technology, 2016)
This qualitative research was carried out using formal key informant group discussions and household semi-structured interview. The objectives of the research were to evaluate food diversity and security of three ethnic groups at Nam Chat village, XiengKhuang province in northern Lao PDR, where the village includes three ethnic groups; Khmu, Hmong and Lao Loum. The study found that rice was the main staple food crop for three ethnic groups. However, Hmong and Khmu representing approximately 30% of total household in this village produced insufficient rice for household consumption. Food was gathered from various kinds of cultivated crops and domestic livestock, and also included wild plants, wildlife aquatic animals and insects. The three ethnic groups consumed different quantities of food sources from crops or animal species, depending on specific ethnic groups. The three ethnic groups earned household income both from crops and domestic animals, as well as from non-timber forest products and wildlife. Lao Loum received per capita income greater than Hmong and Khmu in the present study.